2019
DOI: 10.1111/os.12516
|View full text |Cite
|
Sign up to set email alerts
|

Modified Broström Repair With and Without Augmentation Using Suture Tape for Chronic Lateral Ankle Instability

Abstract: Objective To compare the clinical and radiological outcome between the modified Broström repair with augmentation using suture tape (MBA) and the modified Broström repair (MB) for patients with chronic lateral ankle instability. Methods A retrospective study was performed in Ningbo No. 6 Hospital. The study included 53 patients who underwent surgical treatment from March 2014 to July 2016 and were followed for 2 years. A total of 25 patients underwent modified Broström … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 31 publications
0
79
0
1
Order By: Relevance
“…FAAM total scores were reported in 3 studies, which consisted of 83 ST patients and 86 BR patients. The mean FAAM scores were 89.4 ± 7.4 for the ST group and 92.2 ± 6.5 for the BR group in the study by Cho et al 7 ; 93 ± 13 for ST and 89.3 ± 15 for BR in the study by Ulku et al 52 ; and 93.1 ± 2.3 for ST and 90.5 ± 5.1 for BR in the study by Xu et al 59 No significant difference was found between the ST and BR groups (mean difference [MD], 0.90; 95% CI, –3.17 to 4.96; I 2 = 70%; P = .66) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…FAAM total scores were reported in 3 studies, which consisted of 83 ST patients and 86 BR patients. The mean FAAM scores were 89.4 ± 7.4 for the ST group and 92.2 ± 6.5 for the BR group in the study by Cho et al 7 ; 93 ± 13 for ST and 89.3 ± 15 for BR in the study by Ulku et al 52 ; and 93.1 ± 2.3 for ST and 90.5 ± 5.1 for BR in the study by Xu et al 59 No significant difference was found between the ST and BR groups (mean difference [MD], 0.90; 95% CI, –3.17 to 4.96; I 2 = 70%; P = .66) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 82%
“…The operation time was reported in 3 studies. Xu et al 59 reported there was no significant difference in operation time between groups but provided no detailed data. Ulku et al 52 reported that the mean operation time for the ST and BR groups was 35.2 ± 5.2 and 48.6 ± 5.6 minutes, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations